NILAI-NILAI PENDIDIKAN PADA PEMBERONTAKAN RAKYAT SUMATERA BARAT PADA AWAL TAHUN 1927 (Paramita: Historical Studies Journal, 2011)
Each incident in history contain high values that can be taken and utilized as the guidance for the next generation to be the guide for their life in the future. The history lesson will become really significant if each history teacher always invest the values of education from each kind of history material that is taught to the pupil. The West Sumatera riot revolt at the beginning of 1927 at least contain three values of education that that is good to be socialized to students, firstly, the disintegration of the West Sumatera community contain the value of the importance of the spirit of unity, secondly, authoritarianism the colonial Dutch government in undertaking his authority in West Sumatera contain the value of democracy of the importance of social, political, economic and cultural life, thirdly, tactics of Indonesian Communist Party in inciting the West Sumatera community to carry out the revolt show us the importance of the value of vigilance towards the disturbance and the threat to himself, the community, the nation.   Keywords:, values ​​education, historical events, popular uprising   Setiap kejadian dalam sejarah mengandung nilai-nilai yang tinggi untuk diambil dan memanfaatkan sebagai pedoman bagi generasi berikutnya sebagai panduan untuk hidup mereka di masa depan. Pelajaran sejarah akan menjadi benar-benar signifikan jika setiap guru sejarah selalu menanamkan nilai pendidikan dari materi sejarah yang diajarkan kepada murid. Pemberontakan rakyat di Sumatera Barat pada awal tahun 1927 setidaknya mengandung tiga nilai-nilai pendidikan yang yang baik sebagai bahan pelajaran dan internalisasi nilai murid-murid, pertama, disintegrasi masyarakat Sumatera Barat mengandung nilai pentingnya persatuan, dua, otoritarianisme pemerintah kolonial Belanda dalam melaksanakan kekuasaannya di Sumatera Barat mengandung nilai pentingnya demokrasi dalam kehidupan sosial, politik, ekonomi dan budaya, tiga, taktik PKI dalam menghasut masyarakat Sumatera Barat untuk melaksanakan pemberontakan dapat sarat dengan nilai kewaspadaan terhadap gangguan dan ancaman terhadap dirinya, masyarakat, bangsa.   Kata Kunci:, nilai-nilai pendidikan, peristiwa sejarah, pemberontakan rakyat